Beberapa Faktor yang Berpengaruh terhadap Kejadian Diabetes Mellitus Tipe 2 pada Wanita Usia Subur (WUS) di RSUD Kota Madiun - Hanifah Ardiani; Suharyo Hadisaputro; Djoko Trihadi Lukmono; Heri Nugroho; Antono Suryosaputro (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2018)
Background : Women of reproductive age with Diabetes Mellitus (DM) who were married having a risk complications of pregnancy, either on mother and her baby. Study on risk factors of DM in women of reproductive age was a rare, they have never done on women of reproductive age that married. The objective of this study was to prove some variables that inﬂuence to DM in women of reproductive age.Method : An observasional analytic was conducted with case-control study design. Populations in this study were women of reproductive age 20-49 years that check blood sugar at Madiun Regional Hospital. The samples in this study were 54 cases and 54 controls by consecutive sampling. Data were analyzed by chi-square and logistic regression.Results : Women of reproductive age with 2 and 3 quartile stress scores had risk 4,12 (95% CI=1,42-11,92) and 5,64 (95% CI=1,19-16,55) greater for DM than the comparison group. Women of reproductive age with physical activity <600 MET had risk 4,33 times greater for DM than ≥ 600 MET (95% CI = 1,71-10,96).Conclusion : Variables levels of carbohydrate and fat consumption were not associated with DM. Physical activity and stress levels were evident inﬂuece DM occurence in women of reproductive age.